Structural isomeric aromatic diamine linkers influenced electrocatalysis of AuNPs: Efficient assessment of hydrazine in environmental water samples - Karmegam Muthukrishnan; N.S.K. Gowthaman; Bharathi Sinduja; Mathur Gopalakrishnan Sethuraman (Talanta Open)
This electrochemical research explores the conductive behaviour and sensor functionality of citrate-stabilized gold nanoparticles (AuNPs) constructed on a glassy carbon (GC) electrode. Aromatic diamines (ArDAs) with different structural isomeric forms were used as efficient linkers for the attachment of AuNPs, with particular attention given to the detection of hydrazine (HYZ). Careful analysis of three distinct ArDAs, ortho-phenylenediamine (OPD), meta-phenylenediamine (MPD), and para-phenylenediamine (PPD), revealed the formation of self-assembled monolayers (SAMs) of ArDAs on the GC electrode surface. The growth kinetics of ArDA SAMs on GC surfaces were examined using ATR-FT-IR, focusing on the -NH2 bending vibration region (1592–1631 cm-1), and the Langmuir adsorption kinetics described the SAM formation, specifically, faster and easier formation of PPD-SAM than OPD and MPD. The PPD SAM on the electrode surface was found to be more compact than OPD and MPD, according to the multi-method analysis. The synthesized AuNPs were anchored on the electrode surface through the free amine groups present in the SAMs and confirmed through scanning electron microscopy, X-ray photoelectron spectroscopy, and cyclic voltammetry. The AuNPs/PPD/GC electrode exhibited superior sensitivity (562 µA mM-1 cm-2) and a low detection limit (30 nM) towards HYZ determination. Further, the practicability of the proposed sensor is evaluated by detecting HYZ in environmental water samples and validating the results with the ultra-high-performance liquid chromatography method.